RANCANG BANGUN ROBOT KRI 2012 - Andreas Hadi; Agus Halim; Noor Eddy (Program Studi Teknik Mesin Universitas Tarumanagara, 2014)
Abstract: Designing Robot KRI 2012 is applied in the industrial world that serves as a means of shifting materials. At KRI 2012 the game that took the motto